Comparative bone marrow responses during Trypanosoma congolense infection in N'Dama and Boran cattle - Andrianarivo, A.G.; Muiya, P.; Opollo, M.; Logan-Henfrey, L.L. (International Laboratory for Research on Animal Diseases, 1994)
Anaemia is a major cause of morbidity and mortality in bovine trypanosomiasis and has served as the main parameter to monitor the severity of the disease. In fact, trypanosome-infected cattle experience intermittent episodes of pancytopaenia including anaemia, leucopaenia and trombocytopaenia. Considering the multiple blood cell lineages affected by the disease, it was hypothesized that a defect in the bone marrow, site of origin of those cells, might be a cause. Study of the bone marrow response was intitiated in the laboratory using a Trypanosoma congolense rechallenge infection in five Boran cattle. The cattle developed a non-responsive, normocytic, normocytic, normochromic anaemia during the first ten weeks of the infection, characterized by low levles of erythroid progenitors in the bone marrow. Subsequently, between week 10 and 14, a responsive macrocytic hypochromic anaemia followed, characterized by peaks of CFU-E, slight increase of BFU-E levels and appearance of BFU-E in the peripheral blood. During trypanosome infection the trypanotolerant N'Dama cattle usually develop a moderate anaemia associated with lower parasitaemia when compared to the susceptible Zebu cattle such as the Boran. The present study was undertaken to determine if the ability of the N'Dama cattle to better control anaemia resides in a superior bone marrow response.